One hundred fifty years of total laryngectomies - Hans, Stéphane; Baudouin, Robin; Circiu, Marta P.; Couineau, Florent; Rigal, Tiffany; Remacle, Marc J.; De Vito, Andrea; Cammaroto, Giovanni; Crevier-Buchman, Lise; Lechien, Jérôme R. (Frontiers in Oncology, 2024)
The inaugural total laryngectomy in history was conducted by Billroth in 1873. Nevertheless, significant enhancements to the technique were achieved through the contributions of Gluck, Sorensen, and various other surgeons. Throughout the 20th century, advancements in anesthesia, infectious disease, hospital hygiene, antibiotic therapy, resuscitation, and the expertise of numerous laryngologists elevated total laryngectomy to a pivotal surgical intervention in head and neck surgery.The latter half of the 20th century witnessed a paradigm shift with the emergence of organ preservation protocols. Total laryngectomy became the preferred choice for patients experiencing radiotherapy failure. However, the widespread use of laryngeal conservative treatments appears to be correlated with a decline in overall survival rates in the United States and Europe. The evolution of new minimally invasive surgical approaches in the 21st century may usher in a revolutionary era in the management of laryngeal carcinoma, offering the potential for improved survival and functional outcomes.